The Effect of urea molasses block upplementation on the performance, the blood ammonia and glulcose og sheep - Retno S.W.; Romziah S.B. (Hemera Zoa, 1992)
The experiment was conducted to study the effect of Urea Molasses Block (UMB) supplementation on the performance, the blood ammonia and glucose of sheep. Twelve male sheep on average one year old were used as experimental animals. Thehy were randomly divided into four groups. Hence, each group consisted of three animals. The four treatments applied were PO : control group fed on grass only, P1 : grass supplemented with UMB cantaining 3.6% of urea, P2 : grass supplemented with UMB cantaining 4.8% of urea, P3: grass suplemented with UMB containing 7.2% of urea. The treatments were arranged over the sheep according to Complete Randomized Design with 3 replicates.The results of the experiment showed that UMB supplementation influenced (P < 0.05) the live weight gain, geed consumption and conversion, retention of nitrogen, blood ammonia and glucose of sheep.It was concluded that UMB supplementation did not adversely affect the animal's health and yielded blood ammonia and glucose values in a normal range.With regard to the performance of the sheep, the P3 group fed on grass supplemented with UMB containing 7.2% of urea showed the highest performance.